Grammatical gender reversals: A morphosyntactic and sociopragmatic analysis - Steriopolo Olga (De Gruyter, 2021)
This work analyzes grammatical gender reversals (feminine to masculine and masculine to feminine) in various languages by examining them both morphosyntactically and sociopragmatically, and is, to the best of my knowledge, the first such twofold analysis of grammatical gender reversals. The morphosyntactic analysis is based on my previous works on expressive morphology. The sociopragmatic analysis is based on the sociopragmatic framework developed in Acton (Acton, Eric K. 2014. Pragmatics and the social meaning of determiners. Doctoral Dissertation. Stanford, CA: Stanford University) and presents a continuation and development of my earlier work on sociopragmatics of gender reversals (Steriopolo, Olga. 2019a. “A sociopragmatic analysis of grammatical gender reversals.” In: Con temporary means and methods in ELT and applied linguistics, eds. C. Can, P. Patsala, and Z. Tatsioka, ch. 26: 535–55. Tallinn: LIF – Language in Focus). Grammatical gender reversals result in an evaluative meaning of the noun. I argue that they crosslinguistically use the same syntactic structure, in which an evaluative head [eval] is projected above a categorized noun, n. The evaluative head [eval] changes the grammatical gender of the base to which it attaches, resulting in a gender reversal with an evaluative meaning. This meaning varies across languages and directly depends on the sociocultural context, such as how masculinity and femininity are perceived and valued within a given society. The data presented in this research are, in order of appearance, from the following languages: Russian, Israeli Hebrew, Lak, Polish, Lokono, Teop, Palestinian Arabic, Manambu, Tigre, Maasai, Oromo, Benchnon, Halkomelen, and Alamblak.